Awareness about Different Scholarship Schemes among University Students: A Brief Overview - Santosh; Bora , Mayuri (Research Highlights in Language, Literature and Education Vol. 6, 2023)
This chapter highlights about awareness regarding Different Scholarship Schemes among University Students. Scholarship schemes are intended to recognize and reward a student's academic achievement and educational programmes. Receiving a scholarship is a significant accomplishment. Though a considerable number of scholarship schemes are available in India, the level of awareness regarding scholarship among students is not known. So, in order to find out the level of awareness of the respondents regarding different scholarship schemes the present study was conducted among the students of Assam Agricultural University, Jorhat district of Assam, India. Two hundred forty undergraduate students from different colleges of the University were included as respondents by using a stratified random sample method for the study. One questionnaire was prepared on “Google Form” for online data collection. Frequency, percentage, Mean, Standard Deviation and chi square test were used for analyzing the data statistically. The study reveals that majority (88.75%) of the respondents were aware about State Merit Scholarship followed by 83.75 per cent of respondents about Ishan Udya scholarship, 53.33 per cent were aware about National Talent Scholarship whereas only 2.91 per cent were aware about Financial Support to the Economically Backward Students of the University. Majority of the respondents i.e. 90.00 per cent had senior as source of awareness. Though the level of awareness for two scholarships was good, the awareness for the remaining scholarships was not good among the students. It is important on the part of the University authority to increase the awareness among students regarding different scholarships by various different ways.